MiRNA-12129 Suppresses Cell Proliferation and Block Cell Cycle Progression by Targeting SIRT1 in GASTRIC Cancer. (5th June 2020) - Zhang, Wei; Liao, Kai; Liu, Dongning
Gastric cancer is the most commonly occurring cancer with a rapidly increasing incidence rate worldwide. The underlying molecular mechanisms of gastric cancer require further investigation. MicroRNAs exhibit tissue sensitivity as tumor biomarkers that play a role by promoting tumor growth as oncogenes or tumor suppressor genes. We evaluated the effects of microRNA-12129 on gastric cancer and identified the underlying mechanisms of microRNA-12129. Quantitative real-time polymerase chain reaction was conducted to determine the expression levels of microRNA-12129 and sirtuin 1 in vivo and in vitro, and Western blot analysis was performed to detect sirtuin 1 at the protein level in gastric cancer cell lines. Cell proliferation and cell cycle progression were detected by Cell Counting Kit-8 assay and flow cytometry analysis, respectively. The potential targets of microRNA-12129 were predicted by bioinformatics analysis. The targets of microRNA-12129 were confirmed by luciferase reporter assay and rescue assay. We found that microRNA-12129 was downregulated in gastric cancer tissues and gastric cancer cell lines and was significantly associated with the prognosis of patients with gastric cancer. In addition, microRNA-12129 overexpression suppressed tumor cell proliferation and blocked cell cycle progression. Bioinformatics analysis and luciferase reporter assay suggested that sirtuin 1 was a target of microRNA-12129, and sirtuin 1 expression was negatively related to microRNA-12129. Restoration of sirtuin 1 partly reduced the inhibition of cell proliferation and cell cycle progression induced by microRNA-144. Our results collectively suggested that microRNA-12129 suppressed cell proliferation and cell cycle progression in gastric cancer by targeting sirtuin 1. These findings indicated that manipulation of microRNA-12129 expression could help develop a novel therapeutic strategy for gastric cancer.